How can the European Common Agricultural Policy help halt biodiversity loss? Recommendations by over 300 experts. Issue 6 (30th June 2022) - Pe'er, Guy; Finn, John A.; Díaz, Mario; Birkenstock, Maren; Lakner, Sebastian; Röder, Norbert; Kazakova, Yanka; Šumrada, Tanja; Bezák, Peter; Concepción, Elena D.; Dänhardt, Juliana; Morales, Manuel B.; et al.
Abstract: The European Union's Common Agricultural Policy (CAP) has not halted farmland biodiversity loss. The CAP post‐2023 has a new ''Green Architecture, '' including the new ''Eco‐scheme'' instrument. How can this new Green Architecture help tackle the biodiversity crisis? Through 13 workshops and an online survey, over 300 experts from 23 European Member States addressed this question. From experts' contributions, key principles for success include preserving and restoring (semi)natural elements and extensive grasslands; improving spatial planning and landscape‐scale implementation, including through collective actions; implementing result‐based approaches; and improved knowledge exchange. To maximize the effectiveness of Eco‐scheme for biodiversity, experts highlighted the need to prioritize evidence‐based actions, allocate a sufficient budget for biodiversity, and incentivize management improvements through higher payment levels. Additionally, stronger coherence is needed among CAP instruments. For effective CAP implementation, the European Commission and the Member States should expand investments in biodiversity monitoring, knowledge transfer, and capacity‐building within relevant institutions. The remaining risks in the CAP's ability to reverse the loss of farmland biodiversity still require better design, closer monitoring, greater transparency, and better engagement with farmers. Additionally, greater involvement of scientists is needed to guide the CAP toward restoring farmland biodiversity while accounting for synergies and trade‐offs with other objectives.